2017
DOI: 10.2147/opto.s142718
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blink rate and ocular symptoms during different reading tasks

Abstract: BackgroundReading from tablets is fundamental to modern culture. This study measured differences in the blink rate and symptoms of ocular discomfort in healthy participants during reading from a tablet and a paper book.MethodsForty healthy, normal males subjects were recruited for this study. Subjects were video recorded during reading a text presented on an electronic device (9.7 inch tablet) and a hard copy format, for 15 min. Ocular discomfort experienced during reading was scored using a visual analog scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 29 publications
1
52
1
Order By: Relevance
“…In the same way, some studies have demonstrated that reading conditions or close visual tasks may decrease spontaneous eyeblink rate, which ranges from 10 to 15 blinks/min. 3 , 27 , 28 Accordingly, blink frequency while reading on paper and screen rates were reduced compared to spontaneous blink rate in our study. Although blink frequencies while reading have been studied, no normal values for these measurements have been established in adults, nor children.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…In the same way, some studies have demonstrated that reading conditions or close visual tasks may decrease spontaneous eyeblink rate, which ranges from 10 to 15 blinks/min. 3 , 27 , 28 Accordingly, blink frequency while reading on paper and screen rates were reduced compared to spontaneous blink rate in our study. Although blink frequencies while reading have been studied, no normal values for these measurements have been established in adults, nor children.…”
Section: Discussioncontrasting
confidence: 40%
“…Koslowe et al, 29 reported a blink frequency while reading on screen of 17.15 blinks/min and blink frequency while reading on paper of 15.42 blinks/minute. Abusharha et al 28 found a blink frequency while reading a book of 11.35 ± 10.20 blinks/min and a blink frequency while reading on screen of 14.93 ± 10.90 blinks/min. All these study results coincide with our results, taking into account blink frequency while reading on screen was always greater than blink frequency while reading on paper.…”
Section: Discussionmentioning
confidence: 99%
“… 13 As for the accumulated exposure time; We analyzed studies in which it was concluded, like us, that a longer exposure time results in greater visual symptoms. 20 We were able to measure and evaluate TBUT and damage to the ocular surface and we disagreed with Diaz et al, who mention that electronic devices do not produce organic damage, but rather influence the appearance of fatigue or asthenic symptoms if used in an appropriate manner inadequate; 21 for which we emphasize that the mechanism by which the images are observed in the VDT, unintentionally reduces blinking, producing changes in lacrimal dynamics, 22 , 23 decreases the expression of the meibomian gland and prevents an adequate distribution of the lipoid layer, contributing thus to the development of DED, damage to the ocular surface and eyelid disorders. 23 , 24 …”
Section: Discussionmentioning
confidence: 84%
“…According to [23] depressed people have a low blink rate. It has been reported that the normal spontaneous blink rate is between 12 and 15/min [24]. By getting these mentioned points this feature will generate a report that indicates the depression rate by using the blink rate.…”
Section: A) Research Datasetmentioning
confidence: 97%